Fundamentals of Assurance for Lean Projects. - Wright, Christopher (IT Governance Publishing, 2017)
Explaining the jargon and dispelling the mystique that surrounds Lean, this book provides readers with guidance and tips on performing audits or assurance reviews for Lean projects. --